Research progress and prospect in typical sulfide solid-state electrolytes. (1st November 2022) - Duan, Yi; Bai, Xiangtao; Yu, Tianwei; Rong, Yang; Wu, Yanlong; Wang, Xi; Yang, Junfeng; Wang, Jiantao
Abstract: Due to the potential safety issues of liquid lithium-ion batteries, all-solid-state lithium batteries (ASSLBs) combine with high energy density and safety performance are considered to be a highly promising next-generation battery system. As one of the important components in ASSLBs, different types of solid-state electrolytes (SSEs) are designed to meet the complex requirements in ASSLBs. Among them, sulfides have been widely researched and focused on as a result of the highest ionic transport performance available. However, there are still some challenges to be solved for sulfide SSEs, such as narrow electrochemical window, low moisture tolerance and unstable interface between sulfide SSEs and anode or cathode layers. Herein, this article intends to review the properties of different types of sulfide SSEs and their synthesis methods, interface and electrochemical stability and humidity tolerance. The future application prospects of sulfide SSEs are also discussed. Highlights: according to different crystalline structure of sulfide SSEs, different ion conduction mechanisms are revealed. the main methods of synthesizing sulfide SSEs and their advantages and disadvantages. the stability of sulfide SSEs are analyzed. the different modification methods are proposed to addressing. current challenges facing SSEs are discussed, and perspectives on future research routes for SSEs are provided.